Collective creation in contemporary performance - Syssoyeva, Kathryn Mederos, 1961-; Proudfit, Scott, 1971- (Palgrave Macmillan, 2013)
"Seeking to broaden current understanding of collective creation, this edited volume situates its contemporary practice in the tradition which emerged at the beginning of the twentieth century. The contributors trace the aesthetic, social, and political shifts that have marked this mode of theatre making, from mid-century manifestations as a theatrical expression of the New Left to present-day devising practices. With emphasis on Russia, Europe, and North America, Collective Creation in Contemporary Performance examines collective and devised theatre practices internationally and demonstrates the prevalence, breadth, and significance of collective creation in modern times"--